A pilot open label prospective study of memantine monotherapy in adults with ADHD. (1st May 2013) - Surman, Craig B. H.; Hammerness, Paul G.; Petty, Carter; Spencer, Thomas; Doyle, Robert; Napolean, Siena; Chu, Nicole; Yorks, Dayna; Biederman, Joseph
Abstract: Objectives . Available pharmacotherapies treat some adults with ADHD inadequately. A small literature suggests that glutamate modulation could have effects on ADHD. Methods. Memantine, an N ‐methyl‐d ‐aspartate (NMDA) receptor antagonist, was titrated to a maximum dose of 10 mg BID in 34 adult subjects aged 18–55 who met DSM-IV criteria for ADHD or ADHD NOS on structured interview. Twenty-eight subjects completed 12 weeks exposure. The Adult ADHD Investigator Symptom Report (AISRS), Clinical Global Impression (CGI), a neuropsychological battery sensitive to domains of executive function, and the CANTAB cognitive battery were administered. Paired t -tests compared treated and baseline scores. Results. At week 12, AISRS data showed reduction in total symptoms (–17.5, P < 0.001), inattentive symptoms (−10.6, P < 0.001), and hyperactive symptoms (–6.9, P < 0.01). A total of 44% of subjects had CGI ratings of much or very much improved. Cognitive performance improved in measures of attention, working memory, and other selected executive domains by weeks 6 and 12 (each P < 0.05); simple reaction time declined by week 12 ( P < 0.05). There were no severe adverse events, but mild adverse events were common and six subjects discontinued due to adverse effects. Conclusions. Memantine was largely well-tolerated and associated with improvement in ADHD symptoms and neuropsychological performance. Randomized studies are indicated to confirm whether memantine is a novel therapy for ADHD across the lifespan.